Building networks on the fly [cellular radio]. - Pascoe, R. (IEEE spectrum)
In this paper, the author describes how, in order to communicate digitally, anywhere, any time, cell phones and other devices need built in connectivity, or discovery, software that works automatically over all sorts of networks